Perlindungan Hak-Hak Perempuan dalam Perspektif Hak Asasi Manusia dan Peraturan Perundang-Undangan - Nukeschia Amare Calysta (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2026)
This study aims to analyze the protection of women's rights from a human rights perspective and to examine its implementation within the framework of Indonesian legislation. The research employs a normative juridical method using statutory, conceptual, and human rights approaches. The data were collected through library research involving primary, secondary, and tertiary legal materials. The findings indicate that the protection of women's rights has been firmly established through the 1945 Constitution of the Republic of Indonesia, Law Number 39 of 1999 on Human Rights, Law Number 7 of 1984 concerning the Ratification of the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW), Law Number 23 of 2004 on the Elimination of Domestic Violence, Law Number 12 of 2022 on Sexual Violence Crimes, and other related legislation. These legal instruments have provided a comprehensive framework for protecting women's rights in various sectors. Nevertheless, their implementation has not yet achieved optimal effectiveness due to persistent patriarchal culture, limited public legal awareness, restricted access to justice, and weaknesses in law enforcement. Strengthening the protection of women's rights requires harmonized legal regulations, improved capacity of law enforcement officers, enhanced victim protection services, and broader education on human rights and gender equality to ensure effective and equitable legal protection.